Republic of Moldova : Report on the Observance of Standards and Codes (ROSC) Data Module. (IMF Staff Country Reports; Country Report ;, 2006)
This Report on the Observance of Standards and Codes (ROSC)-data module-provides an assessment of Moldova's macroeconomic statistics against the recommendations of the General Data Dissemination System (GDDS) complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. The assessment reveals that Moldova meets GDDS recommendations for all disseminated statistics with one exception: the nonavailability of data on external public and publicly guaranteed debt service schedule. It also meets, and exceeds in most respects, the recommendations for periodicity and timeliness.